Do Research Findings Apply to My Students? Examining Study Samples and Sampling. Issue 2 (15th March 2017) - Cook, Bryan G.; Cook, Lysandra
Abstract : Special educators are urged to use research findings to inform their instruction in order to improve student outcomes. However, it can be difficult to tell whether and how research findings apply to one's own students. In this article, we discuss how special educators can consider the samples and the sampling methods in studies to examine the relevance of research findings for their students. We describe two approaches for examining the degree to which research findings apply to one's students—the classical generalization model and the case‐to‐case transfer model. We also note additional factors and caveats to consider when evaluating the applicability of research findings, examine the implications of samples and sampling in two research studies, and provide a take‐away message that educators should determine the relevance of research findings for their own students by examining studies' samples and the sampling methods.